Letter from Mayor Salvatore Sanchez Jr. - Salvatore Sanchez Jr.:::Mayor, City of Oxnard:::
Letter from Mayor Salvatore Sanchez, Jr. discussing the interests of the City of Oxnard in regards to the disposal of the Oxnard Air Force Base and a proposed airport.